A spatial interaction model with land use and land value. (August 2018) - Silveira, Paulo; Dentinho, Tomaz Ponce
Highlights: Spatial interaction urban model with land use and land value Systemic cost benefit analysis of climate change Interdisciplinary management of the landscape